Ligand-based drug design - Brown, Nathan (Henry Stewart Talks, 2016)
Graph theory and molecular structure representations, Molecular descriptors, High-throughput and virtual screening, Clustering and diversity selection methods, QSAR: quantitative structure-activity relationship models, Multiobjective de novo design